Phǣn phatthanā Khwāmsư̄trong hǣng Chāt chabap thoptuan (Phō̜. Sō̜. 2557-2559) : čhāk Kānprachum Samatchā Khunnatham hǣng Chāt khrang thī 6 - Phisan Nunklīang (Sūn Khunnatham, 2014)
Conference papers of the sixth meeting of the National Moral Assembly on the plan for promotion of integrity and ethics in the various organizations in Thailand for 2014-2016.